Organisation of Banking Regulation - Wellerdt, Alexander (Springer, 2016)
This book illustrates the interaction of banking regulators and discusses with it related legal and economic challenges. First, the importance of administrative organisations for the implementation of regulatory law towards banks and financial institutions is shown. On this basis five model types of administrative organisations in the field of banking regulation are derived. Thereby, banking regulators can be classified due to their influence on regulatory decisions. Their influence runs from preparation across enforcement to control of regulatory decisions. In particular, the cooperation of the European Central Bank with national banking regulators is analysed. Finally, the main legal and economic arguments of Banking Regulation in the Economic and Monetary Union are discussed.